The new trend for search engine optimization, tools and techniques - Asim Shahzad; Deden Witarsyah Jacob; Nazri Mohd Nawi; Hairulnizam Mahdin; Marheni Eka Saputri (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Search Engines are used to search any information on the internet. The primary objective of any website owner is to list their website at the top of all the results in Search Engine Results Pages (SERPs). Search Engine Optimization is the art of increasing visibility of a website in Search Engine Result Pages. This art of improving the visibility of website requires the tools and techniques; This paper is a comprehensive survey of how a Search Engine (SE) works, types and parts of Search Engine and different techniques and tools used for Search Engine Optimization (SEO.) In this paper, we will discuss the current tools and techniques in practice for Search Engine Optimization.